Prognostic Value of Modified Model for End-Stage Liver Disease Score in Patients Undergoing Isolated Tricuspid Valve Replacement - Xu, Hongjie; Wang, He; Chen, Shisong; Chen, Qian; Xu, Tianyu; Xu, Zhiyun; Sun, Yangyong (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Objective: Though prognostic value of model for End-stage Liver Disease (MELD) score in tricuspid surgery was confirmed, the unstable international normalized ratio (INR) may affect the evaluation effectiveness of MELD score for isolated tricuspid valve replacement (ITVR). The aim of the study was to assess the prognostic value of modified MELD for ITVR. Methods and Results: A total of 152 patients undergoing ITVR were evaluated. Adverse outcome was defined as in-hospital mortality after surgery. The receiver operating characteristic curve analysis demonstrated that modified MELD score with albumin replacing INR (MELD-albumin) score presented well prognostic value (AUC=0.731, p=0.006) for in-hospital mortality. Through Cox regression and further interval validation, MELD-albumin score was identified as an independent predictor for in-hospital mortality. The optimal cut-off value of MELD-albumin was identified as 8.58 through maximally selected log-rank statistics. And restricted cubic spline analysis demonstrated the linear inverse relationship between MELD-albumin and hazard ratio for in-hospital mortality. Kaplan-Meier analysis illustrated that in-hospital mortality increased significantly in high MELD-albumin (MELD-albumin≥8.58) group than in low MELD-albumin group (MELD-albumin<8.58) (p<0.001). Furthermore, high MELD-albumin was associated with lower BMI, the incidence of lower extremities edema and moderate drinking history, and the MELD-albumin score was correlated with the value of AST, ALT and albumin. And the incidence of renal failure (p=0.003) and pulmonary infection (p=0.042) increased significantly in high MELD-albumin group. Conclusion: MELD-albumin score could provide prognostic value for ITVR. And MELD-albumin score was useful in risk stratification and patient selection for TR patients prior to ITVR.